Involvement of human primary somatosensory cortex in vibrotactile detection depends on task demand - Tamè, Luigi; Holmes, Nicholas P. (Elsevier, 2016)
Detecting and discriminating sensory stimuli are fundamental functions of the nervous system. Electrophysiological and lesion studies suggest that macaque primary somatosensory cortex (SI) is critically involved in discriminating between stimuli, but is not required simply for detecting stimuli. By contrast, transcranial magnetic stimulation (TMS) studies in humans have shown near-complete disruption of somatosensory detection when a single pulse of TMS is delivered over SI. To address this discrepancy, we measured the sensitivity and decision criteria of participants detecting vibrotactile stimuli with individually-tailored fMRI-guided TMS over SI, over a control site not activated by vibrotactile stimuli (inferior parietal lobule, IPL), or away from the head (a no TMS condition). In a one-interval detection task, TMS increased participants' likelihood of reporting 'no' target present regardless of site, but TMS over SI also decreased detection sensitivity, and prevented improvement in tactile sensitivity over time. We then measured tactile thresholds in a series of two-interval forced-choice (2IFC) detection and discrimination tasks with lower dependence on response criteria and short-term memory load. We found that thresholds for detecting stimuli were comparable with TMS over SI and IPL, but TMS over SI specifically and significantly impaired frequency discrimination. We conclude that, in accordance with macaque studies, human SI is required for discriminating between tactile stimuli and for maintaining stimulus representations over time, or under high task demand, but may not be required for simple tactile detection.